Physical activity, sedentary time and breast cancer risk: a Mendelian randomisation study - Dixon-Suen, SC; Lewis, SJ; Martin, RM; English, DR; Boyle, T; Giles, GG; Michailidou, K; Bolla, MK; Wang, Q; Dennis, J; Lush, M; Ahearn, TU; et al. (BMJ Publishing Group, 2022)
Objectives Physical inactivity and sedentary behaviour are associated with higher breast cancer risk in observational studies, but ascribing causality is difficult. Mendelian randomisation (MR) assesses causality by simulating randomised trial groups using genotype. We assessed whether lifelong physical activity or sedentary time, assessed using genotype, may be causally associated with breast cancer risk overall, pre/post-menopause, and by case-groups defined by tumour characteristics.